2014
DOI: 10.1158/1055-9965.epi-13-0761
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in True Interval Breast Cancer Reveals Overactivation of the mTOR Signaling Pathway

Abstract: Background: The development and progression of true interval breast cancers (tumors that truly appear after a negative screening mammogram) is known to be different from screen-detected cancers. However, the worse clinical behavior of true interval cancers is not fully understood from a biologic basis. We described the differential patterns of gene expression through microarray analysis in true interval and screen-detected cancers.Methods: An unsupervised exploratory gene expression profile analysis was perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The only similar work for gene expression differences between screen-detected and interval cancers by Rojo and colleagues was performed in 10 samples (33). The authors found the mTOR signaling pathway to be significantly upregulated in interval cancers and concluded that this pathway may mediate their aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The only similar work for gene expression differences between screen-detected and interval cancers by Rojo and colleagues was performed in 10 samples (33). The authors found the mTOR signaling pathway to be significantly upregulated in interval cancers and concluded that this pathway may mediate their aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported differences in molecular characteristics between ICs and screening-detected breast cancers. Rojo et al, (2014) showed differential expression profiles both at gene and protein levels, especially mTOR signaling, which is upregulated in true interval cancers, suggesting that this pathway may mediate aggressiveness. first reported that these two types of breast cancer may have unique underlying biology based on a 77 single-nucleotide polymorphism risk score However, a recent, well-designed study indicated molecular differences between less aggressive screening-detected breast cancer and more aggressive ICs.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray-based gene expression pro ling is widely used in biomedical researchespecially in chronic non-communicable diseases including neurological diseases [8],cardiovascular disease [9], diabetes [10] and cancer [11].In previous studies, most of microarray analysis methods focus on the comparison between normal and diseased conditions [12]. Identi cation of differential gene expression is a widely used analytical strategy for screening of potential biomarkers in diseased state.Several studies microarray-based gene expression have been carried out, however, single microarray dataset have high false positive rates.Therefore, integration of multiple datasets would signi cantly increase the reliability and sensitivity of ndings and reduce false positives.Gene co-expression network analysis, the recent systems biology approach is widely used for analysis of correlation patterns among microarray analysis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%